Role of public funds in sustaining Islamic microfinance based on maqasid approach: a case study of Selangor tabung masjid - Zakariyah, Luqman; Mhd. Sarif, Suhaimi; Ahmad H.Osman, Rahmah; Abdul Rahman, Shukran; Mohd Noor, Azman (2017)
Purpose - Mosque fund, known as Tabung Masjid in Malaysia, is one of the revenues in Islam yet to be developed. A proper management of this revenue in all Muslim countries where Tabarru‘āt (voluntary donations) are collected ought to have sustainability capacity on Islamic microfinance. However, managing these funds to bring about the foreseeability remains untapped. This paper aims to assess ways in which Tabung Masjid is managed in Malaysia.